2018
DOI: 10.3389/fimmu.2018.02222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HTST and Holder Pasteurization on the Concentration of Immunoglobulins, Growth Factors, and Hormones in Donor Human Milk

Abstract: Donor human milk (DHM) is submitted to Holder pasteurization (HoP) to ensure its microbiological safety in human milk banks but this treatment affects some of its bioactive compounds. The objective of this work was to compare the effects of HoP and high temperature short time (HTST) treatments on some bioactive compounds found in DHM. A total of 24 DHM batches were processed in a continuous HTST system (70, 72, and 75°C for 5–25 s) and by HoP (62.5°C for 30 min). The concentrations of immunoglobulins (Igs) A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 97 publications
6
58
1
2
Order By: Relevance
“…Despite recent studies demonstrating new pasteurization techniques, the method of choice and recommended by the Ministry of Health of Brazil for the Brazilian Network of Milk Banks is still the traditional one. 25,26 Corroborating the results presented in this study, Elisia and Kitts also confirmed that the traditional process of pasteurization of breast milk did not significantly affect the antioxidant capacity of human milk, nor the lipid oxidation in human milk, assessed by determining the average concentration of MDA in samples of raw human milk and after pasteurization. 2,27 Our study has two limitations to highlight.…”
Section: Discussionsupporting
confidence: 84%
“…Despite recent studies demonstrating new pasteurization techniques, the method of choice and recommended by the Ministry of Health of Brazil for the Brazilian Network of Milk Banks is still the traditional one. 25,26 Corroborating the results presented in this study, Elisia and Kitts also confirmed that the traditional process of pasteurization of breast milk did not significantly affect the antioxidant capacity of human milk, nor the lipid oxidation in human milk, assessed by determining the average concentration of MDA in samples of raw human milk and after pasteurization. 2,27 Our study has two limitations to highlight.…”
Section: Discussionsupporting
confidence: 84%
“…Milk immunoglobulins are at least partially preserved after standard procedures of milk processing, but the effect is different for the analyzed classes of immunoglobulins. According to Escuder-Vieco and coworkers (44), the most thermostable immunoglobulin is IgG, showing the highest preservation rate (87-101%), followed by SIgA (concentration reduction of 12-46%), and the least IgM (concentration reduction of 27-75%), whereas high-pressure processing of breast milk had no or a small effect on Igs concentration (45,46). However, the available data can differ.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a continuous HTST system that was developed to pasteurize DHM in the HMB-operating environment was designed and validated [15]. This new system ensures the microbiological safety of DHM with minimal heat damage and preserves some bioactive factors, including immunoglobulins, growth factors and hormones, after DHM treatment at 72 • C for at least 10 s [15,16]. Accordingly, the objective of this study was to evaluate the impact of this new HTST system compared to standard HoP on the DHM content of macronutrients, glucose, myo-inositol, selected water-soluble vitamins (thiamine, riboflavin, FAD, vitamin B2, nicotinamide, pyridoxal and cyanocobalamin) and fat-soluble vitamins (vitamin A, α-tocopherol, γ-tocopherol, vitamin D 3 and vitamin 25(OH)D 3 ), as well as the fatty acid (FA) profile and BSSL activity.…”
Section: Introductionmentioning
confidence: 99%